TUGAS DAN WEWENANG LEMBAGA PENEGAK HUKUM DALAM PENEGAKAN HUKUM TERHADAP TINDAK PIDANA ILLEGAL LOGGING - M Chairul Idrah (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
In the criminal law enforcement against illegal logging is necessary duties and powers of law enforcement in accordance with its tupoksi. For the sake of legal certainty and the smooth implementation of a functional relationship with the prosecutors, the basic idea is the country in the field of criminal investigations of forestry need to realize the uniformity, and harmony, and harmony. Form law enforcement coordination in carrying out the task to eradicate the cases llegal logging is a must establish cooperative relationships between the investigator with the prosecutor in the framework of implementation of the tasks of investigation, to prosecute cases in the field of forestry. On the basis of making a joint - the joint functional relationship with respect to their hierarchy - each, in coordination must be set up and maintain and further poured in a decision or instruction together.